2017
DOI: 10.3390/s17112516
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Piezoresistive Properties of Cement Composites with Hybrid Carbon Fibers and Nanotubes

Abstract: Cement-based sensors with hybrid conductive fillers using both carbon fibers (CFs) and multi-walled carbon nanotubes (MWCNTs) were experimentally investigated in this study. The self-sensing capacities of cement-based composites with only CFs or MWCNTs were found based on preliminary tests. The results showed that the percolation thresholds of CFs and MWCNTs were 0.5–1.0 vol.% and 1.0 vol.%, respectively. Based on these results, the feasibility of self-sensing composites with four different amounts of CFs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 43 publications
(72 reference statements)
0
44
0
4
Order By: Relevance
“…전도성재료를 혼입한 시멘트기반 복합재료의 자기센싱 특성을 평가하기 위하여 다음과 같은 저항변화율(Fractional change in resistivity, FCR)이 사용되고 있다 (Lee et al, 2017;Yoo, You, Youn, et al, 2018).…”
Section: 전도성 재료 혼입 콘크리트의 자기센싱 특성평가unclassified
See 2 more Smart Citations
“…전도성재료를 혼입한 시멘트기반 복합재료의 자기센싱 특성을 평가하기 위하여 다음과 같은 저항변화율(Fractional change in resistivity, FCR)이 사용되고 있다 (Lee et al, 2017;Yoo, You, Youn, et al, 2018).…”
Section: 전도성 재료 혼입 콘크리트의 자기센싱 특성평가unclassified
“…여기서   와   는 각각 시작점에서의 저항 그리고 하중이 변화함에 따라 측정된 저항을 의미하고,   과   는 시작점에 서의 비저항 그리고 하중변화에 따른 비저항을 나타낸다. 하중이 가해지는 과정에서 발생하는 부재의 길이 변화가 무시할 만큼 작은 경우 저항변화율은 비저항 변화율과 같다 고 볼 수 있으며, 본 연구에서는 이 저항변화율을 적용하였다 (Yoo, You, Youn, et al, 2018 Yoo, You, Youn, et al, 2018 (Lee et al, 2017;Yoo, You, Youn, et al, 2018…”
Section: 전도성 재료 혼입 콘크리트의 자기센싱 특성평가unclassified
See 1 more Smart Citation
“…While the composites can also achieve extreme gauge factors [16], [20] cost of materials and need of careful handling might make them less desirable for implementation in low budget and rapid prototyping projects. Combating this, it has been shown that introducing chopped carbon fibers (CCF) along with CNT in sensor materials might yield similar sensor properties while greatly reducing production cost [21]. Similar to CNT, CB, and graphene, carbon fibers show piezoresistive properties that can be used to create sensors on their own [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-materials have shown to improve the micro-structure and comprehensive performance of cement-based composites [ 3 , 4 , 5 , 6 ]. Moreover, several studies on self-sensing cement composites which uses nanocomposites have also been reported [ 7 , 8 , 9 ]. Thus, nano-modified cement-based materials are the main technical ways for developing ultra-high-performance concrete (UHPC).…”
Section: Introductionmentioning
confidence: 99%